Exploring Weak Gravitational Lensing Effects by a Regular Black Hole - Durrani, A. K.; Ramadhan, H. S. (Spektra: Jurnal Fisika dan Aplikasinya, 2024)
Gravitational lensing is one of the physical consequences of Einstein’s general theory of relativity, which has been observationally confirmed. This work aims to study the weak gravitational lensing scenario where the lens is a spherically symmetric, charged-nonsingular black hole that asymptotically behaves as the Reissner-Nordström (RN). The difference exists in the higher-order expansion. Therefore, the metric function of the regular charged black hole is expanded up to the fourth order, and the deflection angle is calculated. The thin lens equation is used, leading to five images: two imaginary and three real images. The exact positions of the images and magnification properties are calculated by providing the physical parameters such as mass, charge, and distances. Our calculation shows that the third image position shifted away from the optical axis. The formalism is applied to the case of a supermassive black hole located at the center of our galaxy with the assumption that it has an electric charge.